Knowledge and Power in Classical Islamic Education: A Literature Study on Bureaucratization and Curriculum Standardization - Ibrahim; Ris’an Rusli; Ismail Sukardi; Fitri Oviyanti; Afroza Yasmin Mitu (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study aims to analyze the relationship between knowledge and power in classical Islamic education, particularly from the perspectives of bureaucratization and curriculum standardization. This study employs Michel Foucault's critical theoretical framework on power knowledge relations to analyze how classical Islamic educational institutions became arenas of contestation between religious authority and political power in shaping and legitimizing the curriculum they taught. It employs a qualitative library-based approach to examine how knowledge and authority interact within the classical Islamic educational system. Data were collected through documentation studies, analyzed using content analysis, and validated through source triangulation to ensure scientific credibility. The findings indicate that the relationship between knowledge and power in classical Islamic education is complex and dynamic. Knowledge functions not only as a means of seeking truth but also as an instrument of political legitimacy and social control. The bureaucratization of education led to more structured systems through madrasas and state patronage; however, it also reduced the intellectual independence of scholars and contributed to the homogenization of thought. Meanwhile, curriculum standardization plays a role in improving quality and disseminating certain values, but it may also limit intellectual diversity and critical thinking. These developments potentially lead to stagnation in the intellectual tradition. Nevertheless, this condition also opens opportunities for reconstructing Islamic education to become more dialogical, integrative, and adaptive to contemporary needs without neglecting its foundational scholarly values